Creativity and Creation: Value Concepts - Lidia Ivanovna Shishkina (Управленческое консультирование)
In this article relate to two major modern concepts: creativity and creation. The meaning of these phenomena is considered in relation to the historical and cultural context. It is proved that the concept of creativity is becoming a landmark of the era of civilization, with its characteristics cult of technological progress, pragmatism, the era of democracy and the rule of the masses.